POSSIBILITIES FOR PRESERVING THE RESULTS OF TREATMENT IN PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS AFTER DOSE REDUCTION AND/OR DISCONTINUATION OF BIOLOGICAL AGENTS: A REMARCA STUDY - E. L. Luchikhina; D. E. Karateev; N. V. Demidova; G. S. Gridneva; G. V. Lukina; M. A. Kanonirova; Yu. V. Muravyev; K. A. Kasumova; E. N. Aleksandrova; A. А. Novikov; A. S. Avdeeva (Современная ревматология, 2016)
Russian and international clinical recommendations postulate the possibility of withdrawal of biological agents in patients with rheumatoid arthritis (RA) after the achievement of clinical remission. But it is not clear what would be the results of implementation of these recommendations in clinical practice.Patients and methods. In REMARCA (Russian invEstigation of MethotrexAte and biologicals for eaRly aCtive Arthritis) trial 78 patients (66 females, 12 males, median age 53 years, duration of disease 7 months at inclusion), who were resistant to high doses of subcutaneous (SC) methotrexate (MTX), were treated by combination therapy with SC MT and biologics (adalimumab, certolizumab or abatacept). Patients were investigated every 3 months using DAS28-ESR, SDAI, CDAI indices as disease activity measures.Results. 30 (38.5%) patients (from 78) continued combination therapy. In 47 (60.3%) after achievement of remission or low disease activity (LDA) the therapy was modified to one of two options: 1) in 21 (26.9%) patients doses of biologics were tapered, in some cases to zero; 2) in 26 (33.3%) patients single-step discontinuation of biologics was performed. After 6 months among 47 patients with modification of therapy 27 (57.4%) maintained remission or LDA, in 20 (42.6%) deterioration observed, including 6 (12.8%) patients who lost remission but remained in LDA, and 14 (29.8%) flared (activity increased to moderate or high levels). First modification option was significantly superior to second option regarding the maintaining remission or LDA.Conclusion. In terms of maximum preservation of the results, optimal modification of treatment strategy is the tapering of the dose by the gradual increase in the period between injections of biologics, at least 12 months after reaching the state LDA or clinical remission.